Mongolia : : a centrally planned economy in transition.. - Rana, Pradumna Bickram( 1947-) (Oxford University Press, 1992)
Growing disenchantment with the socialist economic model, the breakdown of the Council for Mutual Economic Assistance bloc, and the advent of perestroika and glasnost in the former Soviet Union and Eastern Europe, form the basis for Mongolia's decision to open its economy and implement a range of economic reforms. In its current effort towards structural change, Mongolia's government has adopted a comprehensive series of reforms aimed at dismantling the central planning system and establishing a market-based economy. The process started in 1986 and gained momentum with the 1990 election of a new government.